2021
DOI: 10.3389/fcell.2021.676364
|View full text |Cite
|
Sign up to set email alerts
|

Role of RNA N6-Methyladenosine Modification in Male Infertility and Genital System Tumors

Abstract: Epigenetic alterations, particularly RNA methylation, play a crucial role in many types of disease development and progression. Among them, N6-methyladenosine (m6A) is the most common epigenetic RNA modification, and its important roles are not only related to the occurrence, progression, and aggressiveness of tumors but also affect the progression of many non-tumor diseases. The biological effects of RNA m6A modification are dynamically and reversibly regulated by methyltransferases (writers), demethylases (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 148 publications
0
7
0
Order By: Relevance
“…The m 6 A RNA modification has been demonstrated by compelling evidence to be essential for mouse spermatogenesis. Studies on knockout models of m 6 A-associated factors, including writers, readers and erasers, have revealed that m 6 A participates in the precise regulation of spermatogonial differentiation, meiosis and spermiogenesis ( 55 , 56 ). Germ cell-specific ablation of the m 6 A methyltransferase complex core catalytic subunit protein METTL3 or scaffolding protein METTL14 with Vasa-Cre causes exhaustion of the spermatogonial stem cell pool due to excessive spermatogonial proliferation ( 37 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…The m 6 A RNA modification has been demonstrated by compelling evidence to be essential for mouse spermatogenesis. Studies on knockout models of m 6 A-associated factors, including writers, readers and erasers, have revealed that m 6 A participates in the precise regulation of spermatogonial differentiation, meiosis and spermiogenesis ( 55 , 56 ). Germ cell-specific ablation of the m 6 A methyltransferase complex core catalytic subunit protein METTL3 or scaffolding protein METTL14 with Vasa-Cre causes exhaustion of the spermatogonial stem cell pool due to excessive spermatogonial proliferation ( 37 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported that HFD resulted in increased m6A methylation levels and METTL3 expression in the myocardium of mice, while decreasing FTO expression and inducing myocardial apoptosis [ 20 ]. In addition, m6A methylation and its regulatory factors are abnormally expressed in testicular diseases, leading to testicular oxidative damage, apoptosis and reproductive dysfunction [ 13 , 15 ]. It was reported that m6A methylation levels and the expression of METTL3 and METTL14 were up-regulated in semen samples of patients with asthenozoospermia [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…m6A RNA modification is regulated by m6A-related genes, including m6A methyltransferases (methyltransferase-like 3 (METTL3), METTL14 and WT1-associated protein (WTAP), termed as “writers”), RNA demethylases (alpha-ketoglutarate-dependent dioxygenase (FTO) and AlkB homolog 5 (ALKBH5), termed as “erasers”) and RNA binding proteins (YTH N6-methyladenosine RNA binding protein 1 (YTHDF1), YTHDF2, YTHDF3, YTH domain containing 1 (YTHDC1) and YTHDC2, termed as “readers”) [ 10 , 11 ]. Recent studies have reported that m6A RNA modification can regulate mammalian spermatogenesis and reproductive function [ 12 , 13 ]. In addition, it has been reported that m6A modification is related to obesity, oxidative stress and apoptosis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among hundreds of types of RNA modifications identified [ 958 ], m 6 A is possibly the most prevalent internal, dynamic, reversible chemical modification identified to date, and plays critical roles in the growth, differentiation, and metabolism of cells [ 952 , 959 ]. An evolutionarily conserved RNA modification, m 6 A RNA methylation is involved in most aspects of RNA processing that may affect the regulation of cellular processes [ 960 ] such as immune modulation [ 961 , 962 , 963 ], fat metabolism [ 964 ], circadian rhythm [ 965 ], fertility [ 966 , 967 , 968 , 969 ], and brain plasticity and development [ 970 ].…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%